40th Thermophysics Conference 2008
DOI: 10.2514/6.2008-4107
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ablation on Radiative Heating for Earth Entry

Abstract: Using the coupled ablation and radiation capability recently included in the LAURA flowfield solver, this paper investigates the influence of ablation on the shock-layer radiative heating for Earth entry. The extension of the HARA radiation model, which provides the radiation predictions in LAURA, to treat a gas consisting of the elements C, H, O, and N is discussed. It is shown that the absorption coefficient of air is increased with the introduction of the C and H elements. A simplified shock layer model is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…This study showed that the convective heating during the peak heating pulse is reduced to essentially zero. Navier-Stokes simulations with coupled radiation 16,17 and coupled radiation and ablation 18 have been performed recently and shown to agree well with past viscous shock layer results.…”
supporting
confidence: 48%
See 2 more Smart Citations
“…This study showed that the convective heating during the peak heating pulse is reduced to essentially zero. Navier-Stokes simulations with coupled radiation 16,17 and coupled radiation and ablation 18 have been performed recently and shown to agree well with past viscous shock layer results.…”
supporting
confidence: 48%
“…The ablation rates for this case were an orderof-magnitude lower than for the 15 km/s Mars-return case. The study by Johnston et al 18 applied the same Laura/Hara analysis considered in this work to the Apollo 4 peak heating condition at 10.2 km/s. The influence of ablation was shown to be less than 3% on the radiative intensity below 6 eV.…”
Section: Past Radiation Measurements With Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…al. 5,6 Whereas these companion papers focus on specific applications, the present paper focuses on the modeling and the numerical details of model implementation. The baseline flow solver is a newly refactored version of the LAURA code 7 that utilizes Fortran 95 modules.…”
Section: Introductionmentioning
confidence: 99%
“…HARA and LAURA have been coupled for radiation with ablation products using a structured-grid flow solver. 2,16 HARA evaluations take about 10 seconds per line of sight on a current-generation central processing unit. In the LAURA/HARA best practices, radiation evaluations are called from every few hundreds to few thousands of LAURA iterations.…”
mentioning
confidence: 99%